Diagnostic potential of routine brain MRI and high-resolution, multi-contrast vessel wall imaging in the detection of internal carotid artery dissection - Xie, Shanshan; Ran, Yuncai; Wang, Xiao; Zhang, Yong; Fu, Qichang; Ren, Yanan; Liu, Juanfang; Teng, Zhongzhao; Cheng, Jingliang (Frontiers in Neurology, 2023)
Objective: Cervical arterial dissection (CAD) is one of causes of stroke mostly located in the extracranial internal carotid artery (ICA). This study aimed to assess the value of routine brain MRI, clinical information and high-resolution, multi-contrast vessel wall MR imaging (hrVWI) for a timely detection of ICA dissection. Methods: One hundred and five patients with CAD and 105 without were recruited. The lesion type was determined based on images from different modalities including brain magnetic resonance imaging (MRI), magnetic resonance angiography (MRA), computed tomography angiography (CTA), digital subtraction angiography (DSA), ultrasonography, and hrVWI and clinical information. Each lesion was reviewed to determine the type following a step-wise procedure by referring to: (1) brain MRI only; (2) brain MRI and clinical information; (3) hrVWI only; and (4) hrVWI, CTA, DSA and clinical information. Results: Patients suffered from CAD had typical clinical presentations of headache, neck pain and/or Horner’s syndrome. Representative imaging signs in the brain MRI included a crescentic or circular iso- or hyper-intensity around the lumen, a curvilinear and isointense line crossing the lumen or aneurysmal vessel dilation. Based on brain MRI only, 54.3% (57/105) of the patients with CAD were correctly classified and the accuracy increased to 73.3% (77/105) when clinical information was combined (P＜0.001) with a high specificity and low sensitivity. Further analysis showed that hrVWI had a superior capability in detecting CAD with sensitivity and specificity of 95.1% and 97.0%, respectively. Conclusion: The combination of brain MRI and clinical information could be used for the diagnosis of CAD and hrVWI should be sought for uncertain cases.